Appropriate Technology-Based Project-Based Learning: 3D Printing Utilization for Learning Media Class - Monica Cahyaning Ratri (Universitas Sanata Dharma, 2022)
Indonesia has more than ten thousand islands, making it an archipelago; therefore, the distribution of learning media and facilities over the country is difficult. This condition may affect the learning material delivery and the student's understanding. Thus, the do-it-yourself (DIY) learning media helps to overcome this condition. We investigated the usefulness of applying appropriate technology through the 3D printing technique to fabricate learning media inspired by local wisdom to meet the needs of learning media. The students were guided by a project-based learning (PjBL) method to find the problem, design their learning media, fabricate it using a 3D printer, and expected to be applied to deliver the teaching material in the class. This study aimed to observe the implementation of the designing process based on theory to reality. A qualitative method and questionnaire were used to measure student's responses. We found that PjBL learning based on a 3D printing project increases students' motivation through creativity and effectiveness in delivering the teaching materials. Furthermore, 3D printed-based learning media can easily be fabricated, producing less waste.